EFFECTIVENESS OF USING MORINGA LEAVES AS AN ANTI-CHLESTROL INGREDIENT IN WOMEN - Rizky Mauliza; Evi Yanti; Riski Dian Ardianti; Fitri Muliani (PT. Radja Intercontinental Publishing, 2026)
Moringa leaves are a plant that can be used to prevent and treat cholesterol. The increasing number of cholesterol sufferers must be taken seriously and addressed. Cholesterol sufferers are also found in Blang Weu Baroh Village, where the number of cholesterol sufferers is 126 people, with 30 suffering from hypercholesterolemia. This problem must be addressed. The community is unaware that Moringa leaves can be used as a medicine for hypercholesterolemia, with only 15% knowing the benefits of Moringa leaves. Therefore, researchers need to see the effectiveness of the use of Moringa leaves as an anti-cholesterol agent. The purpose of this study was to determine the effectiveness of the use of Moringa leaves as an anti-cholesterol agent in women in Blang Weu Baroh Village, Blang Mangat District, Lhokseumawe City. This study used a quasi-experimental design, namely conducting pretest and posttest testing, with a sample size of 30 people. The results of the study showed that the results of the paired sample t-test obtained a significance value of 0.000 < 0.05, which means there is effectiveness in using Moringa leaves as an anti-cholesterol agent for women in the Blang Weu Baroh Village area. The community's cholesterol levels decreased by 18.7 mg/dL after being given Moringa leaves, so it can be interpreted that Moringa leaves are quite effective in reducing community cholesterol levels.